2019
DOI: 10.17581/bp.2019.08113
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Gymnomitriaceae (Marchantiophyta) in the North Pacific

Abstract: Two new liverwort species, Gymnomitrion kamchaticum sp. nov. and Marsupella aleutica sp. nov., are described based on integrative taxonomical approach derived from mor phology, phytogeography and sequence data. Gymnomitrion kamchaticum is morphologically most similar to Gymnomitrion brevissimum, G. mucronulatum and G. pacifi cum, but differs from them by leaf insertion, shape of leaves and leaf cells. Marsupel la aleutica is morphologically somewhat similar to the Holarctic M. emarginata s.l., M. funckii, M. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The p-distance estimation revealed ITS1-2 variability in two sequenced specimens of M. vermiformis that could be incorrect readings (Table 1). Two specimens from remote regions of Taiwan exhibited variability in both ITS1-2 (0.1%) and trnL-F (0.3%) loci, and this finding is consistent with the level of intraspecific variability in the genus Marsupella [9]. The divergence among taxa varies from 2.5 to 4.4% for ITS1-2 and from 3.9 to 8.9% for trnL-F. A 4.6% difference in trnG-intron counts between the Chinese specimen that was first published as M. stoloniformis and the putative Vietnamese specimen was observed (data not shown in Table 1).…”
Section: Resultssupporting
confidence: 73%
“…The p-distance estimation revealed ITS1-2 variability in two sequenced specimens of M. vermiformis that could be incorrect readings (Table 1). Two specimens from remote regions of Taiwan exhibited variability in both ITS1-2 (0.1%) and trnL-F (0.3%) loci, and this finding is consistent with the level of intraspecific variability in the genus Marsupella [9]. The divergence among taxa varies from 2.5 to 4.4% for ITS1-2 and from 3.9 to 8.9% for trnL-F. A 4.6% difference in trnG-intron counts between the Chinese specimen that was first published as M. stoloniformis and the putative Vietnamese specimen was observed (data not shown in Table 1).…”
Section: Resultssupporting
confidence: 73%
“…The predominately Northern Hemisphere liverwort family Gymnomitriaceae currently includes nine genera [ 1 ], of which Marsupella Dumort. is the most speciose, with thirty-three species worldwide [ 1 , 2 , 3 , 4 ], seven of which are recently described and two representing infraspecific taxa elevated to species rank [ 2 , 3 , 4 ]. In Europe, there are currently sixteen accepted species [ 5 ], and in Portugal, six species are reported [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…et Bakalin was recently described based on one specimen collected by W.B. Schofield from Simeonof Island (Mamontov et al, 2019). So far it has been known only from the type specimen (l.c.).…”
Section: Introductionmentioning
confidence: 99%
“…Morphological study of seven specimens identified as Marsupella sparsifolia from Mednyj Island showed that they all belong to Marsupella aleutica. The species has already been described in great detail and the description is published in an open access journal (Mamontov et al, 2019), so we here want to supplement the protologue by focusing on the variability of specimens from different habitats, as well as on the description of some structures (for example, oil bodies, androecia, sporophytes) that were not found before. We consider it useful to pay attention to this species, since it may be found in other regions of the Far East of Russia and Western North America, and provide description of the variability of the species.…”
Section: Introductionmentioning
confidence: 99%